Taphonomy and contextual Zooarcheology of the first Mesolithic hunting station in Thuringia, central Germany, (central Europe) - Karl, Hans-Volker; Paust, Enrico; Safi, Amtyaz (SPC Journal of Environmental Sciences, 2021)
Taphonomy and contextual zooarcheology of the first Mesolithic hunting station in Thuringia, Central-Germany (Central Europe) was the study area of this paper. The new site at Göttern is of special importance as it is the first excavated hunting station in Thuringia. Until now, we have depended upon numerous discoveries of surface finds, special single finds and a few burials, for the exploration of the Mesolithic Era. Bone remains of wild boar/pig, red deer, moose, roe deer, aurochscattle, wild horse, brown bear, wolf/ dog, mouse and birds have been discovered.Â Â